1.36(u-1)-4.2=2.6

Simple and best practice solution for 1.36(u-1)-4.2=2.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.36(u-1)-4.2=2.6 equation:



1.36(u-1)-4.2=2.6
We move all terms to the left:
1.36(u-1)-4.2-(2.6)=0
We add all the numbers together, and all the variables
1.36(u-1)-6.8=0
We multiply parentheses
1.36u-1.36-6.8=0
We add all the numbers together, and all the variables
1.36u-8.16=0
We move all terms containing u to the left, all other terms to the right
1.36u=8.16
u=8.16/1.36
u=6

See similar equations:

| 123=2x-13 | | 3.05(m+1)=18.3 | | 7s+12-6=-9+2 | | 2.97(r+5=17.82 | | 5+8d=26.50 | | 6x-19=8x+3 | | 12w=7w-20 | | 1=-3a-3 | | 5x+9=17-4x+81 | | =-3a-3 | | 3^y=9^-2 | | (x-8+18+(x+2=180 | | y=250000(0.75)^{7} | | 74+2x+8+5=180 | | 8x-11=7x+8 | | 74+2x(+8)+5=180 | | 7-n×9=29 | | 7-n×8=29 | | 54=2x+20 | | 5x-10/2x+8=8 | | 5/1-4x=3/1 | | 9^999=x | | 2.99(s+1)1.6=7.58 | | 3*8=3*1/3(a+5) | | 127=6x-13 | | 3�−39=3b−39=  −78−78 | | 50-q=5+q | | -9(-v-10)=10-v | | 1.07*x=3500 | | 13=-2/3x-7 | | 3(x-7)=12x | | 60.536=9.2j= |

Equations solver categories